Cloud Point Extraction Method for Spectrophotometric Determination of 3-Aminophenol in Environmental Samples - Imran, Alaa Mousa; Dhahir, Saadiyah Ahmed; Muklive, Ahmed Jassim (Universitas Gadjah Mada, 2024)
This work describes the development of new spectrophotometric techniques for 3-aminophenol assessment. The first technique involves using benzidine in an alkaline solution to convert 3-aminophenol into a colored complex. The produced complex has a red color with an absorbance of 462 nm. Between the concentration range 5–14 μg mL−1, Beer's law is obeyed with a correlation coefficient (R2) of 0.99781, a limit of detection (LOD) of 0.0423 μg mL−1, and a limit of quantification (LOQ) of 0.1411 μg mL−1. The recovery was between 87.2–95.43%, the relative standard deviation (%RSD) was 2.40–3.31% and the molar absorptivity was 3.545 × 103 L mol−1 cm−1. Secondly, cloud point extraction (CPE) was used to determine a trace amount of the colored product in the first method, followed by measuring with a UV-vis spectrophotometer. The linearity of the calibration curve was above the range of 5–14 μg mL−1, and the R2 was 0.9988. The LOD and LOQ were found to be 0.0318 and 0.1059 μg mL−1, respectively. The recovery was between 99.49–99.82%, the %RSD was 0.67–2.00% and the molar absorptivity was 4.724 × 103 L mol−1 cm−1. This method was successfully employed for 3-aminophenol detection in several wastewater samples from Rustamiya, under the Al Doura and Diyala bridge.